Self-screening as a tool for assessing the nutritional risk in hospitalized adults (Research, Society and Development, 2022)
The present study aimed to assess the applicability of a nutritional self-screening tool in adults. This is a cross-sectional study, with male and females, admitted to a public hospital in Pernambuco. Nutritional self-screening was performed by eligible patients and by the researcher. The differences between the self-reported and measured weight and height were assessed by Wilcoxon’s test, with subsequent construction of the Bland & Altman graph. The chi-square test measured whether clinical and sociodemographic variables were associated with nutritional risk diagnosed by the researcher. The study included 171 patients, of which 59.1% were females, and mean age 51.7 ± 15.3 years. A considerable percentage (47.9%, n=82) could not screen themselves, mainly because of low education level and and advanced stage of the disease. The mean self-reported weight (68.4 ± 15.0 Kg) was similar to the weight measured (68.2 ± 15.1 kg). According to the Kappa coefficient, the two diagnoses had moderate agreement (k=0.62; p=0.001). The agreements between self-reported and measured weight and height were good, with a bias close to zero. It is concluded that the applicability of the self-screening instrument was not satisfactory, due to the low level of education and lack of understanding by the population studied.